COVID-19-Induced Cytokine Release Syndrome Associated with Pulmonary Vein Thromboses, Atrial Cardiomyopathy, and Arterial Intima Inflammation - Goette, Andreas; Patscheke, Markus; Henschke, Frank; Hammwöhner, Matthias (TH Open, 2020)
Coronavirus disease 2019 (COVID-19) is a viral disease induced by severe acute respiratory syndrome–coronavirus-2 (SARS-CoV-2), which may cause an acute respiratory distress syndrome (ARDS). First reports have shown that elevated levels of inflammatory cytokines might be involved in the development of organ dysfunction in COVID-19. Here, we can present a case of cytokine release syndrome induced by SARS–CoV-2 causing multiorgan failure and death. Of note, we can report on pulmonary vein thromboses as potential source of cerebrovascular embolic events. Furthermore, we present a specific form of an isolated inflammatory atrial cardiomyopathy encompassing atrial myocardium, perivascular matrix, as well as atrial autonomic nerve ganglia, causing atrial fibrillation, sinus node arrest, as well as atrial clot formation in the right atrial appendage. An associated acute glomerulonephritis caused acute kidney failure. Furthermore, all the described pathologies of organs and vessels were associated with increased local expression of interleukin-6 and monocyte chemoattractant protein-1 (MCP-1). This report provides new evidence about fatal pathologies and summarizes the current knowledge about organ manifestations observed in COVID-19.
Keywords: atria; COVID19; fibrillation; pathology; stroke